The Gambia : For a More Inclusive Jobs Agenda - Mungai, Rose; Tien, Bienvenue (World Bank, Washington, DC, 2020)
The objective of this report is to expand our knowledge of the employment challenges facing individuals in The Gambia. The Integrated Household Survey (IHS) 2015/16 on consumption, expenditure, and poverty is the primary data source for the report. This survey offers a comprehensive, nationally representative picture of the country’s jobs market and, in particular, a better understanding of the supply side of jobs. The analysis therefore covers employment structure, worker characteristics, key labor market outcomes for different groups across regions and poverty status, and constraints affecting participation in the labor market. The report focuses on different issues related to employment. It provides an overview of the workforce and discusses issues related to access to jobs. It then elaborates on the composition and quality of employment. The report also discusses human capital and skills building preparedness for future labor demand. It concludes by focusing on options for policy agenda and discusses a set of short-term and medium-term options that could be the basis for an effective jobs strategy in The Gambia.